Determination of the energy release rate function for an eccentrically notched center-loaded beam using elastic fracture analysis - García-Álvarez, Víctor Óscar; Gettu, Ravindra; Carol, Ignacio (Journal of Structural Engineering, 2024)
The center-loaded beam with an eccentric notch is a simple test setup for studying non-planar fracture, which is a common cracking mode in structural elements. This work presents a methodology for obtaining the relations between the energy release rate and crack extension for this geometry, considering two different notch eccentricities. The finite element analysis is based on linear elastic fracture mechanics and the method of virtual crack extension, and can be applied to other geometries and notch eccentricities. Using the energy release rate and the crack path, the mode I and mode II components of the stress intensity factor have been obtained. The crack paths used in the analysis have been obtained from tests of concrete and polymethylmethacrylate beams, in order to study the effect of both tortuous and smooth cracks on the mode II fracture component.